Information Literacy Skills and the Utilization of Information Resources by Public Health Workers in Federal Neuro-Psychiatric Hospital Calabar - Ogunjimi, Blessing Etukudo; Eyong, Isu Usang; Offon, Emem Uwem (Advances in Social Sciences Research Journal, 2022)
This study investigated the influence of “information literacy skills on the utilization of information resources by public health workers in Federal Neuro-Psychiatric Hospital Calabar”. Three research hypotheses were formulated to guide the study. Survey research design was adopted for the study. Purposive sampling technique was utilized to select subjects of the study. Ninety five out of the one hundred and twenty five copies of the questionnaire administered were retrieved and found treatable. A well-structured and validated questionnaire named information literacy skill and utilization of information resources (ILSUIR) questionnaire was used to collect information from respondents. Cronbach’s Alpha reliability method was used to determine the reliability of research instrument, and correlation coefficient range of 0.74 to 0.89 was arrived at. These were considered high enough to justify the conclusion that the instrument is reliable in measuring the variables set for the study. Data obtained were subjected to statistical analyses using Independent t-test analysis. The results revealed that access point, ICT competence and information evaluation skills significantly influenced utilization of information resources by public health workers of Federal Neuro-Psychiatric Hospital Calabar”. Based on the findings it was recommended that library literacy skill programs should be organized by the authorities in the study area in order to update the staff and other users of the library on access point. It was equally recommended that the use of information communication technology (ICT) should be encouraged while evaluation of information resource toward effective library utilization should be carried out periodically.